In vitro antimicrobial activity of Caesalpinia coriaria (Jacq.) Willd extracts on Streptococcus pyogenes and Candida albicans - Silvio Alejandro Lopez-Pazos (Universidad de Antioquia, 2021)
Background: “Dividivi” Caesalpinia coriaria (Jacq.) Willd fruits are traditionally used by the Wayuú community in La Guajira (Colombia) to treat oral and skin cavity diseases caused by bacteria and fungi. Streptococcus pyogenes is a gram-positive cocci of group A (beta-hemolytic) that is the cause of pharyngeal disease, scarlet fever, cellulitis, erysipelas, or toxic shock-like syndrome. Alternatively, Candida albicans is a yeast-like fungus that is a normal flora of the digestive tract, vagina, or skin folds; it has been known to be the root cause of opportunistic diseases such as diaper rash, oral and esophagus thrush, or vulvovaginitis. Objective: This study evaluated the antimicrobial activity of methanolic and ethanolic extracts of C. coriaria (Jacq.) Willd dry fruits on S. pyogenes ATCC 12384 and C. albicans ATTC 14053. Method: C. coriaria extracts were obtained from the Soxhlet method using two solvents (methanol and ethanol 98%) prepared from pulverized fruits. A phytochemical test and an antimicrobial activity assay were performed using the obtained extracts and tested using S. pyogenes ATCC 12384 and C. albicans ATTC 14053 strains. Results: A phytochemical profile was performed, examining the presence of bioactive metabolites (tannins, alkaloids, glycosides, saponins, and anthraquinones) from each extract. Antimicrobial susceptibility tests showed that the ethanolic extract inhibited S. pyogenes ATCC 12384, causing inhibition halos of 14.1 ± 0.1 mm and a Minimum Inhibitory Concentration (MIC) of 172 mg/ml, and C. albicans test shows inhibition halos of 16.1 ± 0.2 mm and MIC of 212 mg/ml. Additionally, the methanolic extract inhibited S. pyogenes with inhibition halos of 15.2 ± 0.2 mm and MIC of 152 mg/ml; no inhibitory effect was observed on C. albicans. Conclusion: This study revealed that C. coriaria has an antimicrobial effect on the tested species opening the field of its possible use as a therapeutic agent.